Synthesis, Spectral, Anticancer Studies on Cu (II) Complex of 2,4,5-Triphenyl-1H-Imidazole - Fahimah Martak; Iin Candrawati; Ayu Widyasari (Jurnal Kimia Valensi, 2016)
Schiff bases of 2,4,5-triphenyl-1H-imidazole ligand and Cu(II) complex has been synthesized and characterized by 1H and 13C NMR, elemental analyses, molar conductance, thermal analysis (TGA), magnetic moment measurement, IR and UV-Vis. On the basis spectral studied and analytical data, it is evident that the Schiff base acts as monodentat ligand coordinating via nitrogen atom. The result showed that Cu(II) complex has octrahedral geometry. The studied complex was tested for anticancer activity. The anticancer activity of Cu(II) complex is evaluated against liver Carninoma (HEPG2)  cell lines. These compound exhibites a moderate and weak activity against HCT 116 cell line with IC50 19.8 mM. DOI: http://dx.doi.org/10.15408/jkv.v0i0.3328